STRATEGIC RETHINKING: COMBINATION OF BALANCED SCORECARD-BASED APPROACH AND FUZZY ANALYTIC NETWORK PROCESS TO ENHANCE THE EDUCATION QUALITY - Sangka, Khresna Bayu (Prosiding Seminar Nasional Pendidikan Akuntansi dan Keuangan, 2015)
ABSTRACTÂ Educational providers should monitor and measure their performance continuously, in terms of delivering qualified education to the students and to improve their accountability. Although the importance of such an assessment process has been stressed in the literatures, policies and regulations, there is no framework that has been proposed to consider all the different relevant factors and determines semantically the level of the quality of education being delivered. In order to provide such an approach, in this paper we propose a framework by which the quality of education being delivered in a subject in an Indonesian university can be determined by using the Balanced Scorecard (BSC). The proposed approach will capture the different factors to be considered from the different perspectives and assimilate them to determine the quality of education. The resultant analysis will provide important inputs to the different stakeholders involved in taking appropriate measures to ensure that studentsâ learning experiences can be maintained at a certain desired level.Â Â ABSTRAKÂ Penyelenggara pendidikan seyogianya menjaga dan menentukan kinerjanya secara berkelanjutan, dalam arti memberikan pedidikan berkualitas kepada siswa dan selalu meningkatkan akuntabilitasnya. Meskipun ulasan mengenai pentingnya proses penilaian telah banyak diulas diberbagai kajian pustaka, kebijakan dan peraturan, tetapi tidak ada kerangka yang secara menyelurh menerangkan bagaimana kualitas pendidikan dapat diraih melalui berbagai macam faktor. Dalam rangka memberikan pendekatan semacam itu, dalam makalah ini kami mengusulkan kerangka kerja dimana kualitas pendidikan yang disampaikan dalam sebuah topik di sebuah universitas di Indonesia dapat ditentukan dengan menggunakan Balanced Scorecard (BSC). Pendekatan yang diusulkan akan menangkap berbagai faktor yang harus dipertimbangkan dari perspektif yang berbeda dan mengasimilasi mereka untuk menentukan kualitas pendidikan. Analisis yang dihasilkan akan memberikan masukan penting kepada para pemangku kepentingan yang terlibat dalam mengambil langkah yang tepat untuk memastikan bahwa pengalaman belajar siswa dapat dipertahankan pada tingkat tertentu yang diinginkan.Â Keywords: Education quality, balanced scorecard, fuzzy analytic network process